Total Synthesis of Desmethyl Macrolide Antibiotics - Andrade, Rodrigo B. (Synlett, 2015)
Macrolide antibiotics occupy a special place in the history of organic chemistry and medicine. This account chronicles the evolution of our approach that ultimately led to the successful total syntheses of four desmethyl (i.e., Me → H) analogues of telithromycin, a semisynthetic derivative of the flagship macrolide antibiotic, erythromycin.1 Introduction2 Project Rationale and Retrosynthetic Analysis3 Lessons Learned from the Total Synthesis of 4,8,10-Tridesmethyl Telithromycin4 Total Synthesis of 4,10-Didesmethyl Telithromycin5 Total Synthesis of 4,8-Didesmethyl Telithromycin6 Total Synthesis of 4-Desmethyl Telithromycin7 Biological Evaluation of Desmethyl Telithromycin Analogues8 Concluding Remarks
Keywords: total synthesis; desmethyl macrolides; ketolide antibiotics; telithromycin; erythromycin